2017
DOI: 10.4236/ojn.2017.711093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adaptive Quizzing as a Practice and Remediation Strategy to Prepare for the NCLEX-RN

Abstract: National Council Licensure Examination-Registered Nurse (NCLEX-RN) outcomes are extremely important to nursing institutions and students for myriad reasons. For students, the NCLEX-RN represents one of the final milestones to conquer before entering a nursing career. Nursing programs monitor NCLEX-RN pass rates as an important gauge of program quality and minimum levels frequently must be met. This study explored the implementation of an adaptive quizzing and learning system as part of an NCLEX-RN preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…House et al (2016) found most students were satisfied using an adaptive quizzing program and felt its use improved their ability to learn. Most studies evaluated the predictive ability of adaptive quizzing programs on NCLEX pass rates (Cox-Davenport & Phelan, 2015;Malkemes & Phelan, 2017;Pence & Wood, 2018). Presti and Sanko (2019) focused on the relationship between adaptive quizzing programs and end-of-program exit exam scores; they evaluated four cohorts in an accelerated bachelor of science in nursing program.…”
Section: Introductionmentioning
confidence: 99%
“…House et al (2016) found most students were satisfied using an adaptive quizzing program and felt its use improved their ability to learn. Most studies evaluated the predictive ability of adaptive quizzing programs on NCLEX pass rates (Cox-Davenport & Phelan, 2015;Malkemes & Phelan, 2017;Pence & Wood, 2018). Presti and Sanko (2019) focused on the relationship between adaptive quizzing programs and end-of-program exit exam scores; they evaluated four cohorts in an accelerated bachelor of science in nursing program.…”
Section: Introductionmentioning
confidence: 99%
“…However, two motives are most prominent Firstly, a desire to determine whether ALT improves the learning outcomes compared to traditional teaching methods or not (Hinkle et al, 2020;Morente et al, 2014). Secondly to enhance the likelihood that students pass final license exams (Malkemes & Phelan, 2017;Presti & Sanko, 2019;Simon-Campbell & Phelan, 2016). A single study is pedagogically motivated by a hypothesis that adaptive technologies may provide an enhancement of case-based learning by personalizing cases to the students' abilities (Hinkle & Moskal, 2018).…”
Section: Motivation For Usementioning
confidence: 99%
“…As students improve, they are given harder questions. Some of the technologies used allow students to design quizzes themselves and provide the students with an overall mastery score (Malkemes & Phelan, 2017;Presti & Sanko, 2019;Simon-Campbell & Phelan, 2016).…”
Section: Technological Interventionmentioning
confidence: 99%
See 2 more Smart Citations